Argumen Inklusivisme Islam: Aplikasi Teori Usul Fikih dalam Tafsir Ali Imran 64 - Maulana Nur Rohman; Ali Fatoni (Wasathiyyah, 2022)
Each era has different problems while the Quran used is still the same. Then every generation of muslims must continue to research the Quran and implements the values it contains to deal with these problems. Incomplete reading of Islamic authoritive sources has resulted in incorerect religios attitude. An exclusif, radical, and monopolistic attitude began to emerge in claims of religion truth which is reflected in social life. Nurcholish Madjid then initiated an inclusive view of Islam by basing it on the verses of the Quran, especially in the keyword kalimat sawa’. His opinion was met with support and opposition from many. With the theory of Ushul Fiqh, a discipline that serves as a forum for analyzing Islamic texts that balances the authority of revelation and reason, this study  tries to read verse 64 of surah Ali Imran in the context of religious moderation.   Karena setiap zaman mendapati problem yang berbeda-beda sementara Al-Quran tetap sama, maka tantangan bagi setiap generasi muslim adalah terus mengkaji Al-Quran dan mengimplementasikan nilai-nilai yang dikandungnya untuk menghadapi permasalahan hidup yang tengah dihadapi di setiap zaman. Pembacaan yang tidak utuh terhadap sumber otoritatif ajaran Islam mengantarkan sikap beragama yang setengah matang. Muncul sikap eksklusif, radikal dan monopolistik atas kebenaran beragama yang diaktualisasikan dalam sikap sosial. Nurcholish Madjid menggagas pandangan Islam inklusif dengan mendasarinya pada ayat-ayat Al-Quran, khususnya pada kata kunci kalimah sawa’. Ia disambut pro-kontra banyak pihak. Dengan teori Usul Fikih, satu disiplin ilmu yang dipandang sebagai alat analisis teks primer Islam yang menyeimbangkan otoritas wahyu dan instrumen akal, peneliti berupaya membaca kembali sikap moderasi beragama pada ayat 64 Ali Imran.